2018
DOI: 10.1080/10903127.2018.1484969
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Frequent Users of Emergency Medical Services in Singapore

Abstract: Frequent EMS users consume a disproportionate amount of healthcare resources. Two broad subgroups of patients were identified: younger patients with social issues and older patients with multiple medical conditions. EMS usage by older patients was significantly associated with higher rates of admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…EDs in Ontario and British Columbia were compared on flow measures for adults and children but did not consider frequent users of EDs [25]. Other studies have examined a single ED or jurisdiction to describe [26,27] or compare [28][29][30] frequent users to other groups. In our study, the Ontario groups had higher acuity than the Alberta groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EDs in Ontario and British Columbia were compared on flow measures for adults and children but did not consider frequent users of EDs [25]. Other studies have examined a single ED or jurisdiction to describe [26,27] or compare [28][29][30] frequent users to other groups. In our study, the Ontario groups had higher acuity than the Alberta groups.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, discharged HSUs in Alberta had about the same mean LOS as discharged controls whereas discharged HSUs in Ontario had a mean LOS about 12 min longer than discharged controls. A study in an urban ED in Ottawa, Ontario showed that 261 highly frequent ED users (patients in the 99th percentile during 2014) with 3164 presentations had a median LOS of 5.2 h (Q1, Q3 3.1, 8.7) [26] and a study in a Singapore ED showed that 243 frequent users (≥4 presentations in 2015) with 1705 presentations had a median LOS of 2h54min (Q1, Q3 1h42min, 5 h) [27] but neither study compare this measure to non-frequent users. These highly frequent ED users had longer median LOS than either of the HSU groups in our study and Ontario HSUs had about the same median as the Singapore frequent users.…”
Section: Discussionmentioning
confidence: 99%
“…The use of prehospital services was therefore not signi cantly determined by the number of inhabitants, but rather other factors played a dominant role. Speci c infrastructural institutions such as nursing homes, where elderly and multimorbid people usually lived, were found almost exclusively in cities and call for emergency services more frequently [41,42,43,44,45]. The anonymity of the city, with the missing support of the family and neighborhood, and the population's increased expectations also caused the number of operations to rise rapidly [46,47].…”
Section: Urban-rural Distributionmentioning
confidence: 99%
“…In urban areas are also more vulnerable population groups (e.g. homeless people), who often presented themselves as frequent users of emergency services [42,45,48,49,50,51].…”
Section: Urban-rural Distributionmentioning
confidence: 99%
“…People who call the emergency ambulance service frequently may be experiencing falls, mental health problems, self-harming, misusing substances including alcohol, or living with chronic conditions. They are often vulnerable, lonely, living in poverty and experiencing a lower quality of life than the general population [7, 8, 1215]. .…”
Section: Introductionmentioning
confidence: 99%